2017
DOI: 10.3892/ol.2017.5680
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases in Vietnamese patients with colorectal cancer

Abstract: Matrix metalloproteinases (MMPs), a family of endopeptidases also known as gelatinases, have been reported to affect the acquisition of the cell proliferative, cell invasive and metastatic phenotype of several types of cancer. In particular, the gelatinases MMP-2 and −9 have been revealed to facilitate tumor growth and invasion in patients with colorectal cancer (CRC). However, it is not known whether the gelatinase activity of MMP-2 and −9 is also elevated in Vietnamese patients with CRC. The activity of MMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Tumor cells need to overcome a series of multiple biological obstacles to form a metastatic tumor. It is known that matrix metalloproteinases (MMPs) contribute to tumor metastasis [31]. MMPs are a family of zinc-dependent matrix-degrading proteases that have a crucial role in tumor metastasis, in which MMP2, MMP9, and MMP14 are the three major proteinases among MMP subfamily members involved in pericellular proteolysis associated with cell migration [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells need to overcome a series of multiple biological obstacles to form a metastatic tumor. It is known that matrix metalloproteinases (MMPs) contribute to tumor metastasis [31]. MMPs are a family of zinc-dependent matrix-degrading proteases that have a crucial role in tumor metastasis, in which MMP2, MMP9, and MMP14 are the three major proteinases among MMP subfamily members involved in pericellular proteolysis associated with cell migration [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…These results also suggested that downregulation of CPEB4 may suppress metastasis process in NSCLC cells. Moreover, MMPs were involved in tumor cells invasion (Bui et al, ), and downregulation of CPEB4 reducing MMP‐2 and MMP‐9 expression has also been shown in breast cancer (Lu et al, ). We also investigated the function of downregulation of CPEB4 on MMPs expression.…”
Section: Discussionmentioning
confidence: 99%